The E-demon of Cyberbullying among Teens - Negi, Surabhi; Magre, Sunita (JOURNAL OF INDIAN EDUCATION, 2017)
his paper explores the phenomenon of cyberbullying among teens. The main purpose is to understand the problems encountered by adolescents due to cyberbullying and how the victim and others can play a key role in this combat. The paper also focuses on how cyberbullying is different from the conventional bullying and mentions the practices that can be taken up to prevent and minimise incidents involving cyberbullying. Opportunities for future research in this area are also outlined.